The loyalty of Muslim customers on the Indonesian Islamic banks: the role of corporate image, satisfaction, and trust - Baziedy Aditya Darmawan (Jurnal Siasat Bisnis, 2018)
This study aims to investigate the factors that affect the loyalty of Muslim customers in Indonesian Islamic banking industry. Based on the literature review, this study uses customer satisfaction, corporate image, and customer trust as variables that are expected in affecting the loyalty of Muslim customers. Data collection was conducted through a survey that involved 274 Muslim customers. The model was tested using hierarchical regression. The results show that customer’s satisfaction and customer’s trust have an important role to build Muslim customers loyalty in Indonesia Islamic banking industry. Furthermore, the results show that customer’s trust function as a mediator role (partially) for the relationship of customer satisfaction and customer loyalty.